Effect of different laser power densities on efficiency of photobiomodulation of mouse fibroblasts in vitro - Düzgören, İpek. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2019., 2019)
The purpose of the present study was to investigate the eﬃciency of photobiomodulation (PBM) with respect to diﬀerent energy and power densities, as well as diﬀerent incubation times on ﬁbroblast cells.Photobiomodulation (PBM) was performed with visible (VIS) laser light at a wavelength of 635 nm. Murine ﬁbroblasts (L929 cell line) were irradiated at 50 mW/cm2, 125 mW/cm2, 200 mW/cm2 of power densities, separately. Laser irradiation time was varied with respect to the selected power density to keep constant the energy density for the laser groups (i.e. 1 J/cm2, 3 J/cm2, and 5 J/cm2). Cell viabilities were determined by MTT (3-(4,5-Dimethyiazol2-yl)-2,5 diphenyltetrazolium bromide) assay test.Results showed that photobiomodulation eﬀect was determined by energy density, power density, and incubation time. It can be proliferative or none and even under some circumstances inhibitory. For future studies, same paradigm should be tested with in vivo models.|Keywords : Photobiomodulation (PBM), Power density, Photochemical reaction, Low level laser application, Proliferation, Optimal dose, Incubation time.
Keywords: Lasers -- Therapeutic use.; Phototherapy.; Fibroblasts.